SPE Annual Technical Conference and Exhibition 1996
DOI: 10.2118/36670-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Drilling Variables on Barite Sag

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractBarite sag is a significant variation in mud density caused by the settlement of barite or other weight material in high-angle wells. The wide fluctuations in mud weight can lead to severe operational problems, including well-control, induced wellbore instability, downhole mud losses, and stuck pipe.A laboratory flow loop has been used to evaluate the influence of key drilling parameters on barite sag. Results show that the highest sag occurs at angles in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 12 publications
2
34
0
Order By: Relevance
“…Hanson et al (2) have investigated the phenomenon and found that most of the sagging occurs while the mud is circulating. The same conclusion was reached by Bern et al, (3) the sagging tendency is highest at low annular velocities. Zamora and Jefferson (4) presented a method for tracking drilling fluid density variations, which helps to detect, but not to predict drilling mud instability.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Hanson et al (2) have investigated the phenomenon and found that most of the sagging occurs while the mud is circulating. The same conclusion was reached by Bern et al, (3) the sagging tendency is highest at low annular velocities. Zamora and Jefferson (4) presented a method for tracking drilling fluid density variations, which helps to detect, but not to predict drilling mud instability.…”
Section: Introductionsupporting
confidence: 83%
“…It was shown by Bern et al (3) that rotation of the drill pipe will counteract barite separation. When the particles are brought to the high side of the borehole through rotational flow they will settle towards the centre of the borehole, i.e., in the opposite direction of the transported particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high density and acid-soluble option is Mn 3 O 4 (Bern et al 1996). Svendsen et al (1995) introduced Mn 3 O 4 to potassium formate drilling fluid to increase its density to 106 lbm/ft 3 (1698 kg/ m 3 ).…”
Section: Weighting Agents In Drilling Fluidsmentioning
confidence: 99%
“…Bern et al 10 presented a comprehensive analysis of these important variables and provided recommendations in key areas involving well planning and operational practices. Several important findings from this study were later verified by Dye et al 9,11 Both studies identified a critical annular velocity of 100 feet per minute, above which dynamic barite sag is reduced.…”
Section: Introductionmentioning
confidence: 99%